1992
DOI: 10.1007/bf00316882
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ornithine decarboxylase by parathyroid hormone in osteoblastic cell systems

Abstract: Parathyroid hormone (PTH) has been shown to induce osteoblastic activity via a complex signal transduction process which is mediated either by cAMP or cytosolic calcium ([Ca2+]i), or a combination thereof. One of the PTH functions in osteoblasts is the induction of ornithine decarboxylase (ODC) activity. We have analyzed the second messengers involved in this process. 8-Bromo cAMP, a cAMP derivative, enhanced ODC activity in UMR106-01 osteoblastic cell system. The calcium ionophore A23187 and the protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…L-lysine is an essential factor for bone collagen synthesis, and its deficiency will lead to reduced bone collagen synthesis. It can not only affect bone collagen metabolism, but also change physical properties of bone collagen fibers ( Cheng et al, 1992 ). Fini M found that the synthesis of N-type collagen was increased by adding arginine and lysine in cultured osteoporotic rat osteoblast in comparison with the control group ( Tsai et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…L-lysine is an essential factor for bone collagen synthesis, and its deficiency will lead to reduced bone collagen synthesis. It can not only affect bone collagen metabolism, but also change physical properties of bone collagen fibers ( Cheng et al, 1992 ). Fini M found that the synthesis of N-type collagen was increased by adding arginine and lysine in cultured osteoporotic rat osteoblast in comparison with the control group ( Tsai et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lysine, an essential amino acid, is thought to promote human development, enhance immune function, and improve the function of central nervous tissue. Lysine is also an essential factor for bone collagen synthesis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%